1998
DOI: 10.1183/09031936.98.12030716
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis: immunopathogenetic concepts and their clinical application

Abstract: Our understanding of the immunopathogenesis of sarcoidosis has been advanced by studies of bronchoalveolar lavage cells. Activated macrophages and T-cells have been identified in different compartments of the sarcoid lung and the characteristics of the activation suggest that the cells become activated in the course of a normal immune response. The immune cells communicate via a cytokine network and the measuring of cytokine levels yields subgroups of sarcoidosis patients with different courses of the disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
144
1
12

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(161 citation statements)
references
References 254 publications
(309 reference statements)
4
144
1
12
Order By: Relevance
“…These issues have been extensively reviewed in previous papers [3,4]. However, in spite of intriguing findings, the unsuccessful attempt to isolate any given agent consistently or to create reproducible animal models failed to support the hypothesis that an infectious agent underlies sarcoidosis [4].…”
Section: Environmental Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…These issues have been extensively reviewed in previous papers [3,4]. However, in spite of intriguing findings, the unsuccessful attempt to isolate any given agent consistently or to create reproducible animal models failed to support the hypothesis that an infectious agent underlies sarcoidosis [4].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Nevertheless, contrasting results obtained in the search for mycobacterial deoxyribonucleic acid (DNA) in sarcoid tissues do not rule out a possible role of these agents, at least in a subset of subjects with sarcoidosis [30]. This concept fits with the oligoclonality of the disease [3]; in other words, an oligoclonal T-cell activation would be elicited by a still elusive "sarcoid agent".…”
Section: Environmental Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many cytokines and chemokines play an important role during the processes of sarcoid granuloma (17). On the basis of recent Th1 and Th2 paradigms, the cytokine profile of sarcoidosis is Th1 dominant when disease activity is high (17)(18)(19). Recent studies have demonstrated enhanced expression of IL-12 (20 -22) and IL-12R (23,24) in sarcoid lungs.…”
mentioning
confidence: 99%
“…Although the aetiology of sarcoidosis remains uncertain [17], extensively conducted research has revealed several of the histopathologic and immunopathogenic events which occur during the development of noncaseating granulomas and might interpret the aforementioned redox imbalance [18,19].…”
Section: Discussionmentioning
confidence: 99%